Dealing with an international clientele : communications, diplomacy and etiquette - Meredith, Meri (Information services management., 2004)
This book is aimed at all librarians and information professionals working in culturally diverse environments, whether in an academic, public or commercial setting. It addresses the issues of communication, diplomatic etiquette and common courtesies from a wide range of cultures and of how to provide library services across cultural boundaries and languages. Each chapter clearly defines a different aspect and provides clear guidance and strategies for librarians to follow in their everyday work. The book is packed with advice on how to deal with many of the situations, which arise as the resul.